Efficient Systems for the Securities Transaction Industry- A Framework for the European Union - Baris Serifsoy; Marco Weiß (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2003)
This paper provides a framework for the securities transaction industry in the EU to understand the functions performed, the institutions involved and the parameters concerned that shape market and ownership structure. Of particular interest are microeconomic incentives of the industry players that can be in contradiction to social welfare. We evaluate the three functions and the strategic parameters - the boundary decision, the communication standard employed and the governance implemented - along the lines of three efficiency concepts. By structuring the main factors that influence these concepts and by describing the underlying trade-offs among them, we provide insight into a highly complex industry. Applying our framework, the paper describes and analyzes three consistent systems for the securities transaction industry. We point out that one of the systems, denoted as 'contestable monopolies', demonstrates a superior overall efficiency while it might be the most sensitive in terms of configuration accuracy and thus difficult to achieve and sustain.
urn:nbn:de:hebis:30-15327
Keywords: F36; G28; G34; L22; P51; 330; EU; centralcounterparty; clearing; consistent systems; efficiency; regulation; settlement; straight-through processing; trading; Wertpapierhandel; Börse; Wirtschaftliche Effizienz; EU-Staaten